Beginning KeystoneJS : a practical introduction to KeystoneJS using a real-world project - Panati, Manikanta (Apress, 2016)
Learn how to develop a complete and robust Node, express.js and MongoDB-based web application and mobile application backend quickly using KeystoneJS. You'll learn how KeystoneJS makes complicated things simple, without limiting the power or flexibility of node.js or the frameworks it is built on. Beginning KeystoneJS shows you how to build database-driven websites, applications, and APIs, all built upon Express, the defacto web server for Node.js that uses MongoDB as its storage backend. What You Will Learn Discover the setup and architecture of the KeystoneJS framework. See how easy it is to extend KeystoneJS Understand the custom types and fields provided out of the box Write clean markup and create templates using Swig Use the powerful editing options in the framework's responsive dashboard Who This Book Is For Technical and non-technical people who would like to build applications quickly to leverage structured data to improve productivity.